Effect of 3D printing on supply chain management. (2020) - Varsha Shree, M.; Dhinakaran, V.; Rajkumar, V.; Bupathi Ram, P.M.; Vijayakumar, M.D.; Sathish, T.
Abstract: The recent revolution in the field of manufacturing is 3D printing or Additive Manufacturing (AM). Recently, AM technology is emerging as an eye opener for creating complex geometries with desired material and to improve the designing and modelling of implausible structures. It leads to the disruptive innovations that creates a global impact on the logistics of industries and the supply chain. The main competence of this technology is to fabricate the products closer to the expectations of customers around the world and to customize those products in real time. It has great advantages over supply chain management by the means of reduction in inventory, shipping costs and capital expenditures on factories and warehouses which provides the potential to evaluate the transformation of global supply chain management. The main objective of this review is to achieve knowledge on utilization and contribution of 3D printing on supply chain management and to explore the impacts of AM in supply chain management.